Tanggungjawab Ahli Waris Dan Kewenangan Majelis Pengawas Notaris Dalam Penyelesaian Protokol Minuta Hilang (Studi tentang Notaris yang Meninggal Dunia) - Riky Rustam (Officium Notarium, 2021)
This study aims to raise the issue on the position of the Minute of Protocol of Notary Deed as a State Archive as stipulated in the Archives Act, analyze the responsibility of the heirs of a Notary who died for the missing Minute of Protocol and explain the authority of the Regional Supervisory Council to resolve the missing Minute of Protocol after the notary’s death. The method used in this research is normative study by collecting data through library research, using a normative and conceptual approaches as well as qualitative descriptive analysis. The results of this research conclude that the Notary Protocol is a state archive based on the provisions of the Notary Position Act, but not the archive criteria referred to in the Archives Law. The heirs are responsible to the parties who make an authentic deed to the Notary, this responsibility is based on the provisions of Article 1365 of the Criminal Code on Unlawful Acts. Then, the Notary Supervisory Council does not have the authority to give sanctions to heirs who eliminate the Notary Protocol. In the event that the Notary protocol is missing or incomplete, the Regional Supervisory Council shall make a detailed and complete report on this matter.Keywords: Heirs; missing minute of protocol; notary supervisory councilAbstrakPenelitian ini bertujuan untuk mengemukakan permasalahan mengenai kedudukan Protokol Minuta Akta Notaris sebagai Arsip Negara sebagaimana ketentuan Undang-Undang Kearsipan, menganalisa mengenai pertanggungjawaban ahli waris dari Notaris yang meninggal dunia atas Protokol Minuta yang hilang dan menjelaskan kewenangan Majelis Pengawas Daerah untuk menyelesaikan Protokol Minuta hilang setelah meninggalnya Notaris. Metode yang dipakai dalam penelitian ini adalah penelitian normatif dengan mengumpulan data secara studi pustaka (library research), menggunakan pendekatan norma dan pendekatan konseptual serta analisis secara deskriptif kualitatif. Hasil penelitian ini menyimpulkan bahwa protokol Notaris merupakan arsip negara berdasarkan ketentuan Undang-Undang Jabatan Notaris, namun bukan kriteria arsip yang dimaksud dalam Undang-Undang Kearsipan. Ahli waris bertanggungjawab kepada para pihak yang membuat akta autentik kepada Notaris, tanggungjawab ini adalah berdasarkan ketentuan Pasal 1365 KUHPerd tentang Perbuatan Melawan Hukum. Kemudian, Majelis Pengawas Notaris tidak memiliki kewenangan untuk memberikan sanki kepada ahli waris yang menghilangkan Protokol Notaris. Dalam hal terjadi protokol Notaris yang hilang atau tidak lengkap, maka Majelis Pengawas Daerah membuat berita acara mengenai hal itu secara terperinci dan lengkap.Kata Kunci: Ahli waris; majelis pengawas notaris; protokol minuta hilang